Telomere Length in Preterm Infants: A Promising Biomarker of Early Adversity and Care in the Neonatal Intensive Care Unit? - Provenzi, Livio; Scotto di Minico, Giunia; Giorda, Roberto; Montirosso, Rosario (Frontiers in Endocrinology, 2017)
Preterm infants present an immature neurobehavioral profile at birth, even in absence of severe brain injuries and perinatal complications. As such, they require a long-lasting hospitalization in the Neonatal Intensive Care Unit (NICU), which is thought to grant at-risk newborns’ survival, but still entails a number of physical, painful and socio-emotional stressors. Hence, preterm birth and NICU stay represent an early adverse experience, which has been linked to detrimental consequences for neurological, neuro-endocrinal, behavioral and socio-emotional development, as well as to health and disease later in life. Telomeres are the terminal portion of chromosomes and are known to get shorter with age. Moreover, telomere length is affected by the exposure to stress during early development. As such, telomere length might be an innovative biomarker of early adverse exposures in young infants and children. Unfortunately, there is paucity of studies investigating telomere length in populations of preterm infants and its association with known NICU-related stressors remains unexplored. In the present paper, the potential relevance of telomere length for research and clinical work with preterm infants will be underlined in the light of recent contributions linking progressive telomere shortening and early exposure to adverse experiences and stressful environments in humans. Finally, insights will be provided to guide clinically relevant translational research on telomere length in the field of VPT birth and NICU stay.